WORKSHOP TEACHING ENGLISH FOR YOUNG LEARNER MELALUI WORD CHAIN GAME - Dahler Dahler; M. Fadhly Farhy Abbas; Herdi Herdi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2017)
This community service is based on the needs of the teachers at Madrasah Ibtidaiyah (MI) Al-Barokah Pekanbaru in improving and enriching their knowledge about English Language Learning Strategy. Based on the needs analysis, most the teachers at the school feel that their knowledge about teaching strategy is still less, therefore their knowledge should be improved more. Based on this thing, the team needs to conduct workshop which aims at improving as well as enriching the teachers knowledge towards teaching strategy by using Word Chain Game. This activity done in one day which has been divided into 2 sessions. In the first session, the teachers were provided with the knowledge of Word Chain Game. Then, in the second session the teachers were asked to apply the strategy based on the previous explanation. After conducting the workshop, it can be stated that the teachers are able to understand well the implementation of Word Chain Game, and they are able to apply it in the teaching and learning process.